Effect of Zinc and Magnesium Fertilizers on the Yield and Some Characteristics of Wheat (Triticum aestivum L.) Seeds in Two Years - Farhad Sadeghi; Abbas Rezeizad; Mehdi Rahimi (International Journal of Agronomy)
In order to study the interaction effects of zinc and magnesium fertilizers on wheat (cv. Sivand) yield and other characteristics, a factorial experiment was carried out based on a randomized complete block design (RCDB) using four replications. Four levels of zinc sulfate (0, 20, 40, and 60 kg ha−1) and four levels of magnesium sulfate (0, 70, 140, and 210 kg ha−1) were used in this study. The parameters studied included germination, plant height, tillering, 1000-seed weight, hectoliter weight, concentrations of zinc and magnesium in seeds, protein content, and yield. The effects of zinc sulfate and magnesium sulfate for most traits were significant (p<0.01). The highest grain yield (7.68 Ton ha−1) was obtained by applying 60 kg ha−1 of zinc and consuming 140 kg of magnesium per hectare. The maximum magnesium amount in seed was shown in treatment with 60 kg ha−1 of zinc × 210 kg ha−1 magnesium, which was 0.352 mg kg−1. Treatments with the best economic aspects were 20 kg ha−1 of zinc sulfate × 70 kg ha−1 magnesium sulfate and 40 kg ha−1 of zinc × 140 kg ha−1 magnesium, in terms of using less zinc and magnesium fertilizers and having a favorable impact on the attributes. The application of these treatments on wheat can ultimately increase zinc and magnesium in wheat grain. Because these elements play a role in human health, the use of these treatments in wheat can increase zinc and magnesium in wheat grains, and therefore, an effective step can be taken in human health by producing these wheat. According to the test results, the application of 60 kg ha−1 of zinc sulfate along with 140 kg ha−1 of magnesium sulfate can play an important role in increasing wheat yield with reduced costs.